Mesenchymal Stromal Cells Modulate Monocytes Trafficking in Coxsackievirus B3-Induced Myocarditis. (3rd January 2017) - Miteva, Kapka; Pappritz, Kathleen; El-Shafeey, Muhammad; Dong, Fengquan; Ringe, Jochen; Tschöpe, Carsten; Van Linthout, Sophie
Abstract: Mesenchymal stromal cell (MSC) application in Coxsackievirus B3 (CVB3)-induced myocarditis reduces myocardial inflammation and fibrosis, exerts prominent extra-cardiac immunomodulation, and improves heart function. Although the abovementioned findings demonstrate the benefit of MSC application, the mechanism of the MSC immunomodulatory effects leading to a final cardioprotective outcome in viral myocarditis remains poorly understood. Monocytes are known to be a trigger of myocardial tissue inflammation. The present study aims at investigating the direct effect of MSC on the mobilization and trafficking of monocytes to the heart in CVB3-induced myocarditis. One day post CVB3 infection, C57BL/6 mice were intravenously injected with 1 x 10 6 MSC and sacrificed 6 days later for molecular biology and flow cytometry analysis. MSC application reduced the severity of myocarditis, and heart and blood pro-inflammatory Ly6C high and Ly6C middle monocytes, while those were retained in the spleen. Anti-inflammatory Ly6C low monocytes increased in the blood, heart, and spleen of MSC-treated CVB3 mice. CVB3 infection induced splenic myelopoiesis, while MSC application slightly diminished the spleen myelopoietic activity in CVB3 mice. Left ventricular (LV) mRNA expression of the chemokines monocyte chemotactic protein-1 (MCP)−1, MCP-3, CCL5, the adhesion molecules intercellular adhesion molecule-1, vascular cell adhesion molecule-1, the pro-inflammatory cytokines interleukin-6, interleukin-12, tumor necrosis factor-α, the pro-fibrotic transforming growth factorβ1, and circulating MCP-1 and MCP-3 levels decreased in CVB3 MSC mice, while LV stromal cell-derived factor-1α RNA expression and systemic levels of fractalkine were increased in CVB3 MSC mice. MSC application in CVB3-induced myocarditis modulates monocytes trafficking to the heart and could be a promising strategy for the resolution of cardiac inflammation and prevention of the disease progression.